Images-characters of Fedir Dudko’s collection of short stories "Girls of Desperate Days" - Khomyshyn, Olga (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2023)
The proposed article analyzes the specifics of the creation of character images in the collection "Girls of Desperate Days" by Fedir Dudko, the determinism of the behavioral model of the character world by the idea of patriotism, which permeates the ideological-thematic and artistic-figurative levels of the collection, as well as the genre specifics of the novel, in which the image-character is revealed at the moment of the highest tension. The research methodology is outlined by using hermeneutic and interpretive methods, elements of the structural approach and the biographical method. The results of the study prove that the idea of national identity, patriotism determines the specificity of the grouping of images-characters of the collection, the originality of central images-characters creation, inspired by passionate energy. As befits the novelistic genre works, these images are revealed unexpectedly, at the moment of danger. If the heroine image is not central, it is modeled to a large extent by the internal state nuance. It can be stated that biographical synergism plays a significant role in the creation of the "psychological background", mood of the novel.